Kepemimpinan Kiai: (Analisis Modalitas Kepemimpinan Kiai Kampung Dalam Tradisi Kompolan) - Syafiqurrahman Syafiqurrahman; Mohammad Hosnan (Tafhim Al-'Ilmi, 2019)
Besides being a Qur’an teacher, the leader of village (Kiai) become community leaders; almost all aspects of people's lives were deferred to the kiai, ranging from religious, educational, social, political, and so on, including the village kiai becoming the traditional leaders of the Kompolan. village kiai use the characteristics of charismatic-collective leadership and transformative leadership. While the capital used is cultural, symbolic modality, which then gives birth to economic capital. Under his leadership, Kompolan was able to contribute to creating an atmosphere of togetherness and unity among individuals in society, developing and strengthening religious knowledge, contributing to empowerment in the economic sector of society, creating a space of actualization for the community. Selain menjadi guru ngaji, kiai kampung juga menjadi pemimpin masyarakat; hampir dalam semua aspek kehidupan masyarakat ditangguhkan kepada kiai, mulai dari persoalan keagamaan, pendidikan, sosial, politik, dan seterusnya, termasuk kiai kampung menjadi pemimpin tradisi kompolan. kiai kampung menggunakan karakter kepemimpinan karismatik-kolektif dan kepemimpinan transformatif. Sedangkan modal yang digunakan adalah modalitas kultural, simbolik, yang kemudian melahirkan modal ekonomi. Di bawah kepemimpinannya, kompolan mampu memberikan kotribusi dalam menciptakan suasana kebersamaan dan kebersatuan antar individu di masyarakat, pengembangan dan pemantapan ilmu keagamaan, memberikan sumbangsih pemberdayaan di bidang ekonomi masyarakat, menciptakan ruang aktualisasi bagi masyarakat. Kata Kunci (Keyword): Kepemimpinan, Kiai Kampung, Tradisi Kompolan.